The Chemical Probes Portal: an expert review-based public resource to empower chemical probe assessment, selection and use. Issue Volume 51:Issue D1(2023) (21st October 2022) - Antolin, Albert A; Sanfelice, Domenico; Crisp, Alisa; Villasclaras Fernandez, Eloy; Mica, Ioan L; Chen, Yi; Collins, Ian; Edwards, Aled; Müller, Susanne; Al-Lazikani, Bissan; Workman, Paul
Abstract: We describe the Chemical Probes Portal (https://www.chemicalprobes.org/ ), an expert review-based public resource to empower chemical probe assessment, selection and use. Chemical probes are high-quality small-molecule reagents, often inhibitors, that are important for exploring protein function and biological mechanisms, and for validating targets for drug discovery. The publication, dissemination and use of chemical probes provide an important means to accelerate the functional annotation of proteins, the study of proteins in cell biology, physiology, and disease pathology, and to inform and enable subsequent pioneering drug discovery and development efforts. However, the widespread use of small-molecule compounds that are claimed as chemical probes but are lacking sufficient quality, especially being inadequately selective for the desired target or even broadly promiscuous in behaviour, has resulted in many erroneous conclusions in the biomedical literature. The Chemical Probes Portal was established as a public resource to aid the selection and best-practice use of chemical probes in basic and translational biomedical research. We describe the background, principles and content of the Portal and its technical development, as well as examples of its applications and use. The Chemical Probes Portal is a community resource and we therefore describe how researchers can be involved in its content and development.